Brazilian Academy of Neurology recommendations for diagnosis, management, and treatment of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) - Nascimento, Osvaldo J. M.; Marques Jr, Wilson; Gonçalves, Marcus Vinícius Magno; Tomaselli, Pedro José; Pupe, Camila; França Jr, Marcondes Cavalcante; Gondim, Francisco de Assis Aquino; Freitas, Marcos Raimundo Gomes de; Frezatti, Rodrigo Siqueira Soares; Oliveira, Acary Souza Bulle; Rotta, Francisco Tellechea; Tosta, Elza Dias; Scola, Rosana; Daccach, Vanessa; Marrone, Carlo Domenico; Becker, Jefferson; Rigatto, Susanie; Martinez, Alberto R. M.; Cabeça, Hideraldo; Winckler, Pablo Brea; Dourado, Mario Emilio; Santos, Diogo Fernandes dos (Arquivos de Neuro-Psiquiatria, 2025)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an acquired autoimmune disorder that leads to progressive motor and sensory impairment, resulting in significant morbidity. While the incidence rates vary, CIDP remains a challenging condition requiring a standardized and optimized approach to diagnosis and management. In Brazil, a middle-income country with substantial regional disparities in healthcare access, the availability of specialized neuromuscular centers is uneven, creating obstacles to timely and effective treatment. To address these challenges, the Brazilian Academy of Neurology (Academia Brasileira de Neurologia, ABN, in Portuguese) has developed national recommendations for the diagnosis, management, and treatment of CIDP, tailored to the country's healthcare resources. This consensus outlines standardized diagnostic criteria that incorporate electrophysiological and imaging findings, and it emphasizes key differential diagnoses to enhance diagnostic accuracy. The recommendations were developed through expert panel discussions and a non-systematic review of the literature. The recommended treatment strategies include first-line therapies such as corticosteroids, intravenous immunoglobulin (IVIg), and plasmapheresis, with guidance on escalation and titration of immunosuppressive therapy in refractory cases. By emphasizing early intervention to prevent axonal degeneration and disability, these guidelines aim to improve clinical outcomes and support public health policies within the Brazilian National Health System (Sistema Único de Saúde, SUS, in Portuguese), ensuring equitable and effective CIDP management across the country.
Keywords: Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Consensus; Diagnosis; Therapeutics